Synthesis and photopolymerizations of first monomers with phosphonate and bisphosphonate or phosphonic and bisphosphonic acid functionalities for potential dental applications. Issue 24 (21st October 2018) - Gencoglu, Turkan; Duman, Fatma Demir; Olcay, Keziban; Acar, Havva Yagci; Avci, Duygu
ABSTRACT: The first monomers containing both phosphonate and bisphosphonate (M1) or phosphonic and bisphosphonic acid (M2) functionalities are synthesized, aiming to improve binding abilities of self‐etching adhesive systems and composites: An amine having both phosphonate and bisphosphonate functionalities is prepared via Michael addition reaction between diethyl (6‐aminohexyl)phosphonate and tetraethyl vinylidene bisphosphonate, its reaction with 2‐isocyanatoethyl methacrylate gives M1 which is converted to M2 by selective dealkylation of the phosphonate/bisphosphonate ester groups. Their copolymerization with commercial dental monomers (bisphenol A glycidyl methacrylate, triethylene glycol dimethacrylate, and 2‐hydroxyethyl methacrylate) investigated by photo‐differential scanning calorimetry shows adequate photopolymerization rate and conversion. X‐ray diffraction, Fourier transform infrared, and X‐ray photoelectron spectroscopy analyses of M2‐treated hydroxyapatite particles show formation of stable M2‐calcium salts. These monomers are assessed to be not toxic according to MTT standards by in vitro cytotoxicity studies with NIH 3T3, U2OS, and Saos‐2 cells. All these properties make these monomers potential candidates as biocompatible components for dental adhesives and composites. © 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 2739–2751 Abstract : To improve efficiencies of dental materials, novel monomers containing both phosphonate and bisphosphonate/phosphonic and bisphosphonic acid are synthesized. Interaction of monomers with hydroxyapatite (mineral structure of teeth) is analyzed; their copolymerization rate and yield with the dental monomers are evaluated by using photo‐differential scanning calorimetry.